Microworld simulations for command and control training of theater logistics and support staffs : a curriculum strategy - Bondanella, J. (John), 1944- (RAND, 1999)
This report discusses changes in training structure, content, and methods, with the focus on developing training for CSS staffs operating as staffs, not for individual training. The focus is on large unit staffs: corps and echelons above corps headquarters and support commands. The document discusses shortcomings of the current approach to CSS staff training, and then proposes a process-oriented approach. It illustrates how microworld models can be used to train CSS processes. It then goes on to describe how pilot testing of prototype models indicates that this approach is feasible for large unit staffs. It concludes with a proposed training strategy that the authors believe is more appropriate and useful for meeting the challenges posed to the Army by personnel turbulence, split-based operations, increased reliance on information, and decreased training resources. The authors believe this approach has applications beyond the CSS training environment. They argue that the microworld models in a carefully designed training strategy are appropriate to any business that needs to train staff under distributed conditions in uncertain environments and to avoid time- and resource-intensive costs of bringing staff together for a large game in a central location.
Prepared for the United States Army by Rand's Arroyo Center.
At head of title: Rand.
"December 1998."
"MR-929-A"--Page 4 of cover
Keywords: United States. -- Army -- Management.; United States. -- Army; Command and control systems -- United States.; Military education -- United States -- Simulation methods.; Commandement militaire -- États-Unis.; HISTORY -- Military -- Biological & Chemical Warfare.; Command and control systems; Armed Forces -- Management; Military education -- Simulation methods; United States